(untitled) (Eurasian Scientific Herald, 2023)
In order for students to develop the ability to communicate in a non-native language, they must have a common culture of communication, the main provisions of which are the ability to choose in relation to each of the participants in the conversation a method of communication that would not diverge from the rules of speech communication and at the same time best respond would be the individual characteristics of those with whom you have to communicate.